Assessing the electrical activity of individual ZnO nanowires thermally annealed in air. Issue 4 (24th January 2022) - Bah, Micka; Tlemcani, Taoufik Slimani; Boubenia, Sarah; Justeau, Camille; Vivet, Nicolas; Chauveau, Jean-Michel; Jomard, François; Nadaud, Kevin; Poulin-Vittrant, Guylaine; Alquier, Daniel
Abstract : The electrical activity of ZnO NWs is assessed using scanning capacitance microscopy with the aim of determining their dopant homogeneity relative to their reduced dimensionality, the Debye screening length and annealing temperatures in air ambiance. Abstract : ZnO nanowires (NWs) are very attractive for a wide range of nanotechnological applications owing to their tunable electron concentration via structural and surface defect engineering. A 2D electrical profiling of these defects is necessary to understand their restructuring dynamics during engineering processes. Our work proposes the exploration of individual ZnO NWs, dispersed on a SiO2 /p ++ -Si substrate without any embedding matrix, along their axial direction using scanning capacitance microscopy (SCM), which is a useful tool for 2D carrier profiling. ZnO NWs are hydrothermally grown using 0–20 mM ammonium hydroxide (NH4 OH), one of the reactants of the hydrothermal synthesis, and then annealed in a tube oven at 350 °C/1.5–15 h and 450 °C/15 h. While the as-grown ZnO NWs are highly conductive, the annealed ones exhibit significant SCM data with a high signal-to-noise ratio and temperature-dependent uniformity. The SCM signal of ZnO NWs is influenced by both their reduced dimensionality and the electron screening degree inside them. The electrical activity of ZnO NWs is only observed below a critical defect concentration that depends on the annealing temperature. Optimal SCM signals of 200 and 147 mV are obtained for samples with 0 and 20 mM NH4 OH, respectively, and annealed at 350 °C/15 h. The corresponding electron concentrations of 3.27 × 10 18 and 4.58 × 10 18 cm −3 were estimated from the calibration curve, respectively. While thermal treatment in air of ZnO NWs is an effective approach to tune the defect density, 2D electrical mapping enables identifying their optimal electrical characteristics, which could help to boost the performance of final devices exploiting their coupled semiconducting–piezoelectric properties.